Assembly and operation of bacterial tripartite multidrug efflux pumps. Issue 5 (May 2015) - Du, Dijun; van Veen, Hendrik W.; Luisi, Ben F.
Highlights Multidrug efflux pumps in Gram-negative bacteria can be assembled in tripartite structures to enable transport across the cell envelope. The structure of a full tripartite assembly illuminates the drug transport mechanism.